Escape from Fort Bravo [videorecording (DVD)] - Sturges, John, 1910-1992; Holden, William, 1918-1981; Parker, Eleanor, 1922-2013; Forsythe, John, 1918-2010 (Warner Home Video, 2008)
Any Johnny Reb who tries to escape the Union prison outpost at Fort Bravo faces the unforgiving Arizona Territory desert stretching out before him ... and the even more unforgiving pursuit of Bravo's resolute Captain Roper. Yet there's a common foe that may unite the Civil War rivals: the fierce Mescalero horsemen waging guerilla war against Blue and Gray alike.